Efficacy of Mixed Model Instruction to Improve English Language Skills of Business Management Students: An Experimental Study - Alam, Sohaib (Journal of Education Culture and Society, 2024)
Aim. The current study explored and compared the efficacy of technology-based instructions, specifically web-mediated, blended, and online instructions, on the enhancement of English language skills among students pursuing Business management  (BM) in Prince Sattam Bin Abdulaziz University, Saudi Arabia.Method. A total of two hundred and four participants were chosen randomly and divided into four groups. The control group, comprising 51 individuals, received general English instruction utilizing the communicative language teaching (CLT) approach, and engaged in exercises that focused on developing their general English skills. On the other hand, the web-mediated learning experimental group, also consisting of 51 participants, received general English instruction through the Duolingo educational model. Similarly, the blended experimental group, comprised of 51 individuals, received general English instruction through the Enriched Virtual Blended Learning Model. Lastly, the online learning group, consisting of 51 participants, received general English instruction through the LMS instructional model.Results. Prior to the intervention, all students underwent a pretest, and subsequently, a posttest and a delayed posttest were administered to evaluate their proficiency in standard general English, as measured by the TOEFL exam. The study's results indicated that all groups displayed progress in their English language skills. However, the Duolingo and Enriched Virtual learning models demonstrated superior performance in enhancing English language skills compared to the other groups.Conclusion. These findings hold significant pedagogical implications for curriculum designers, the development of training programs for future HR professionals, material producers, and all stakeholders involved in the field of BM education.